P385 Candida auris: a growing threat to global health. (20th September 2022) - Varma, Sharin; Srivastava, Smriti; Sharad, Neha; Kiro, Vandana; Ningobam, Aparna; Mathur, Purva
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Background and Objectives: The emerging pathogen, C. auris, has been associated with nosocomial outbreaks in recent times. The true scale of the problem is difficult to comprehend due to several issues with the identification of C. auris using both phenotypic and molecular techniques. Most commonly, these isolates have been misidentified as C. haemulonii . Biofilm formation is strongly suggested given its association with intensive care settings, especially in patients with CVCs and long-term urinary catheters. Many isolates of C. auris have also shown raised MICs to multiple classes of antifungal agents, raising the possibility of pan-drug resistance. Objective: To study the demographic characteristics, risk factors, and outcomes in patients with C. auris infection. Methodology: This is a retrospective study from a tertiary care hospital (JPNATC, AIIMS) including all patients from the time period of 2018-2022 that showed growth of C. auris in any site. C. auris was identified using conventional methods (pale-pink growth on chromogenic medium, no pseudohyphae on germ-tube test, growth in presence of 10% NaCl) and VITEK-2. To reduce the misidentification and the intertest variability, the results were confirmed with MALDI-TOF. The risk factors and other patient information were taken from the HIS. Statistical analysis was performed. Results: During the study period, a total of 31 patients had a C. auris infection. The most common age group was 20-40 years ( n  = 11, 44%) with a preponderance in males ( n  = 23, 74%). A total of 74% of the infections were found in blood, which was the most common site of infection followed by urine (10%). The other sites were pus-from-wound ( n  = 2), groin, nailbeds, and CVP tip ( n  = 1). Most of the cases were ICU patients (86%). All the patients with candidemia due to C. auris ( n  = 17 100%) had CVC, had surgery within the past 30 days, and were on broad-spectrum antibiotics and TPN. 71% (n = 12) had a history of immunosuppression and 18% ( n  = 14) had a history of prior antifungal therapy. Although 100% ( n  = 17) had the presence of an indwelling urinary catheter, none of them had candiduria due to C. auris . No patient with C. auris infection had neutropenia. The median LOS was 34.5 days. Most of the isolates were resistant to fluconazole ( n  = 13, 93%), amphotericin B ( n  = 13, 93%), voriconazole ( n  = 6, 55%), flucytosine ( n  = 10, 71%). A total of 87% ( n  = 12, 87%) of isolates were sensitive to caspofungin and micafungin by VITEK-2 (limitation of this study). In all, 28% ( n  = 7) of the patients died whereas 40% ( n  = 10) were discharged. A total of 75% patients had clearing of the persistent candidemia when treated with caspofungin whereas only 25% patients had clearing of the candidemia when treated with voriconazole. Conclusion: Most cases of C. auris infection were found in critical patients with the most common presentation being candidemia. The risk factors are similar to any other Candida infection. C.auris is the leading antimicrobial-resistant fungi and poses an additional burden to the healthcare system. The fungus has a high crude-mortality rate and we are running out of treatment options. A comprehensive intervention program with ongoing surveillance and good AMR practices is the need of the hour to reduce the burden of this dangerous pathogen.